Review on biodegradable microsphere with special emphasis on inflammatory bowel disease & recent patents - Supriya Shidhaye; Krutika Nagpurkar; Mayur Kale; Ruchi Khobragade; Milind Umekar; Shreya Koche; Rashmi Trivedi (Next Nanotechnology)
Inflammatory Bowel Disease (IBD) encompasses two major forms: Crohn's disease and ulcerative colitis, characterized by chronic inflammation of the gastrointestinal tract. These conditions present unique challenges in drug delivery due to the need for precise targeting of affected regions while minimizing systemic side effects. Biodegradable microspheres offer a promising solution, providing sustained, localized drug release that enhances therapeutic efficacy and patient compliance. Comprised of naturally degradable polymers, these microspheres encapsulate drugs, ensuring targeted delivery to inflamed sites and reducing systemic exposure. This review explores the potential of biodegradable microspheres in IBD management, emphasizing their role in addressing current drug delivery challenges. Key advantages include sustained drug release, improved drug stability, and the ability to reduce adverse effects. Recent advancements and patents are discussed, focusing on innovative microsphere formulations and targeting strategies that enhance therapeutic outcomes. Additionally, the significance of biodegradable polymers in enabling site-specific drug release is highlighted, showcasing their transformative potential in IBD therapy.